ORODISPERSIBLE TABLETS: A REVIEW - Roy, Anupam (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Orally disintegrating tablets (ODTs) are solid dosage forms containing drugs that disintegrate in the oral cavity within less than 1 minute leaving an easy-to-swallow residue. The European Pharmacopeia adopted the term orodispersible tablet for a tablet that disperses or disintegrates within <3 minutes in the mouth before swallowing. ODT is a good choice of drug delivery for pediatric and geriatric patients because it troubleshoots the problem of dysphagia. The current article is focused on ideal characteristics, advantages and disadvantages, various technologies developed for ODT, evaluation methods along with recent research and future potential. Keywords: Orodispersible tablets, Mechanism of disintegration, Fast dissolving films, Recent research.